Organizational Emergence: The Origin and Transformation of Branson, Missouri's Musical Theaters - Chiles, Todd H.; Meyer, Alan D.; Hench, Thomas J. (Organization Science, 2004)
We draw on complexity theory to explain the emergence of a new organizational collective, and we provide a much-needed empirical test of the theory at the collective level of analysis. Taking a case study approach, we use four dynamics of emergence posited by complexity theory's dissipative structures model—fluctuation, positive feedback, stabilization, and recombination—to explain how a collective of live musical performance theaters in Branson, Missouri, came into being and periodically transformed itself over a 100-year period. Our findings suggest a strong match between the theoretical perspective employed and the empirical processes uncovered, empirically validating the model at the collective level. The study demonstrates the value of conceptualizing evolution in terms of emergence, highlighting distinctions between the nascent complexity approach to evolution and the neo-Darwinian evolutionary approach that has dominated the theoretical conversation in organization science for the past generation. Our findings complement the insights of the dominant theoretical perspectives in organization theory, providing a more comprehensive understanding of organizational evolution by directly addressing the heretofore intractable phenomenon of emergence.